Small and medium-sized banks (Publications Office of the European Union, 2023)
Less significant institutions (LSIs), with the exception of cross-border LSIs, are under the direct responsibility of national resolution authorities (NRAs) with SRB oversight ensuring effective and consistent application of the Single Resolution Mechanism (SRM) Regulation and high standards in resolution planning and crisis management both horizontally - across the LSIs in the 21 participating Member States - and vertically - between the LSIs and SRB banks within these Member States. In terms of the sector's structure, about three quarters of the LSIs belong to several cooperative and savings banking networks. These networks - three of which comprise both significant institutions (SIs) and LSIs - are not prudentially consolidated. For this reason, from a resolution perspective, resolution planning, including the public interest assessment (PIA), and resolvability assessments are performed individually at the level of each institution in the network. Of the remaining 500 LSIs, half are characterised by traditional business models and the other half follow special business models such as custodian, investment bank or financial market infrastructure (FMI). At the end of the 2022 resolution planning cycle (RPC), 25 of the 68 LSIs with the resolution strategy had a shortfall with respect to the final targets of the minimum requirements for own funds and eligible liabilities (MREL). The cumulative MREL shortfall stood at EUR 3.5 billion, which is 3.8% of the total risk exposure amount (TREA) including the capital buffer requirement (CBR), and EUR 220 million, which is 0.7% of the leverage ratio exposure measure (LRE). The MREL transitional period has been extended beyond 1 January 2024 for 10 of these LSIs. The NRAs did not formally identify any substantive impediments to resolvability in the 2022 RPC. The NRAs' phasing in and proportionate implementation of the SRB's Expectations for Banks (EfB) and the 'heatmap' approach is ongoing. The NRAs and the SRB are jointly enhancing LSI crisis preparedness and management through discussion of the NRAs' best practices and enhancing SRB procedures. Going forward, the current macroeconomic situation may pose some challenges to some LSIs, in particular for those that are vulnerable to interest rate risk. LSIs' reliance on non-covered deposits as source of funding represents another point to monitor, considering also the increased potential mobility of deposits due to the widening use of social media and further digitalisation across the entire LSI sector. On 18 April 2023, the European Commission adopted a proposal to further strengthen the EU's bank crisis management and deposit insurance (CMDI) framework. Inter alia, the CMDI proposal addresses some of the key challenges identified by the SRB LSI oversight in 2022.
10.2877/275060
Keywords: Graue Literatur; Amtliche Publikation; Bank; Bankrisiko; KMU; EU-Staaten; banking; credit institution; investment company; banking policy; resolution; banking system